2019
DOI: 10.3390/jcm8091496
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide and Levosulpiride Use and Subsequent Levodopa Prescription in the Korean Elderly: The Prescribing Cascade

Abstract: The aim of this study was to investigate the prescribing cascade phenomenon of dopaminergic drugs such as levodopa in the management of gastroprokinetic drugs induced parkinsonism. Based on the Korea National Health Insurance Service (NHIS)-Senior Cohort Database, we analyzed patients aged ≥65 years, between 2009 and 2013, who obtained new prescriptions for levodopa through the NHIS during this period. Those who were prescribed levodopa from 2002 to 2008 were excluded, only patients who were prescribed metoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 20 publications
1
28
1
2
Order By: Relevance
“…Prescribing cascades are situations in which multiple treatments and conditions interact and intersect leading to diagnostic errors and preventable drug‐related morbidity. One high‐priority prescribing cascade described includes: (1) calcium channel blocker → edema→ diuretic therapy 2,3 . Calcium channel blockers (CCB) are associated with lower‐extremity edema, and loop diuretics have been used inappropriately to treat CCB‐associated lower extremity edema, constituting a prescribing cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing cascades are situations in which multiple treatments and conditions interact and intersect leading to diagnostic errors and preventable drug‐related morbidity. One high‐priority prescribing cascade described includes: (1) calcium channel blocker → edema→ diuretic therapy 2,3 . Calcium channel blockers (CCB) are associated with lower‐extremity edema, and loop diuretics have been used inappropriately to treat CCB‐associated lower extremity edema, constituting a prescribing cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Those in the high exposure group (>30 mg/day and/or duration >5 days) had a 1.83 fold higher risk than standard users (≤30 mg/day and/or duration ≤5 days). In another study from Korea, metoclopramide and levosulpiride users above 65 years of age had almost threefold odds of beginning levodopa therapy relative to non‐users (metoclopramide: OR = 2.94; 95% CI = 2.35–3.67 and levosulpiride: OR = 3.30; 95% CI = 3.52–4.32) 9 . Compared to those who received a shorter duration of the drug (<20 days), the risk of initiation of levodopa therapy for both metoclopramide and levosulpride users increased with increasing duration of therapy beyond 20 days.…”
Section: Discussionmentioning
confidence: 96%
“…In another study from Korea, metoclopramide and levosulpiride users above 65 years of age had almost threefold odds of beginning levodopa therapy relative to non-users (metoclopramide: OR = 2.94; 95% CI = 2.35-3.67 and levosulpiride: OR = 3.30; 95% CI = 3.52-4.32). 9 Compared to those who received a shorter duration of the drug (<20 days), the risk of initiation of levodopa therapy for both metoclopramide and levosulpride users increased with increasing duration of therapy beyond 20 days. Another case-control study from Korea also reported a higher risk of parkinsonism with exposure to propulsive drugs (OR = 2.82; 95% CI = 2.46-3.21), antipsychotics (OR = 3.0; 95% CI = 1.67-5.43), and flunarizine (OR = 4.95; 95% CI = 2.71-9.04) in the year before the first date of diagnosis of parkinsonism, 8 compared with never users.…”
Section: Discussionmentioning
confidence: 97%
“…The low incidence of this prescribing cascade in NSSPBD compares favourably with other jurisdictions. In a Korean population of adults over 60 years of age, those prescribed metoclopramide were about three times more likely to be prescribed levodopa than those who were not (OR 3.04; 95% CI (2.46-3.77) (4). They also demonstrated that the odds of levodopa prescription increased with increasing duration of metoclopramide treatment (2.82 times for days 1-19 and 4.14 times for > 20 days; both odds ratios were adjusted for age, sex and exposure to antipsychotic medications) (4).…”
Section: Discussionmentioning
confidence: 99%